2022
DOI: 10.3390/e24070849
|View full text |Cite
|
Sign up to set email alerts
|

Entropy-Weight-Method-Based Integrated Models for Short-Term Intersection Traffic Flow Prediction

Abstract: Three different types of entropy weight methods (EWMs), i.e., EWM-A, EWM-B, and EWM-C, have been used by previous studies for integrating prediction models. These three methods use very different ideas on determining the weights of individual models for integration. To evaluate the performances of these three EWMs, this study applied them to developing integrated short-term traffic flow prediction models for signalized intersections. At first, two individual models, i.e., a k-nearest neighbors (KNN)-algorithm-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 46 publications
0
13
0
Order By: Relevance
“…The use of the entropy weight method in this study for calculating index weights is supported by existing literature, which suggests its effectiveness in providing a comprehensive and objective evaluation for decision-making studies [40]. The findings, therefore, gain credibility through the application of this widely accepted methodology.…”
Section: Discussionmentioning
confidence: 52%
“…The use of the entropy weight method in this study for calculating index weights is supported by existing literature, which suggests its effectiveness in providing a comprehensive and objective evaluation for decision-making studies [40]. The findings, therefore, gain credibility through the application of this widely accepted methodology.…”
Section: Discussionmentioning
confidence: 52%
“…Qu et al (2022) established an energy consumption model based on the Elman algorithm in studying energy consumption in cloud computing environments and energy-saving scheduling tasks. They found that the accuracy of the energy consumption model based on the Elman algorithm is higher than that of the multiple linear regression model [37]. They proved the correctness of this paper to study the comparison method between the CNN algorithm and the Elman algorithm in CDC energy consumption.…”
Section: Discussionmentioning
confidence: 58%
“…This measure is employed to mitigate potential estimation biases, and we employ the entropy weight method for this re-evaluation. The entropy weight method has a well-established presence in comprehensive evaluation contexts dealing with multidimensional evaluation indices (Qu et al, 2022). This method assigns greater weight to indices with a pronounced influence in a comprehensive evaluation system.…”
Section: Alternative Measure Of Digital Affordancementioning
confidence: 99%